Shish-kebab type MnCo2O4@Co3O4 nanoneedle arrays derived from MnCo-LDH@ZIF-67 for high-performance supercapacitors and efficient oxygen evolution reaction - Zhou, Jiao-Jiao; Han, Xue; Tao, Kai; Li, Qin; Li, Yan-Li; Chen, Chen; Han, Lei (Chemical engineering journal (Lausanne, Switzerland : 1996), 2018)
The shish-kebab type MnCo2O4@Co3O4 nanoneedle arrays were fabricated by annealing an inorganic complex of MnCo-LDH nanoneedle and ZIF-67 rhombic dodecahedral to act as electrode materials for high-performance supercapacitors and as electrocatalysts for efficient oxygen evolution reaction. [Display omitted] •The shish-kebab type nanoneedle array was prepared via an improved MOF-template-directed strategy.•The resulting MnCo2O4@Co3O4 exhibit high areal capacitance and excellent cycling stability.•The red light-emitting diode (LED) can be illuminated about 6 min by two connected asymmetric supercapacitors.•The MnCo2O4@Co3O4 exhibits much better electrocatalytic activity for oxygen evolution reaction. One-dimensional micro-/nanostructure arrays with excellent synergistic effect have attracted considerable interest for their potential applications in energy storge and conversion devices. In this work, the uniform ZIF-67 rhombic dodecahedron penetrated CoMn-LDH nanoneedle arrays were firstly synthesized and then transformed into shish-kebab type MnCo2O4@Co3O4 nanoneedle arrays by thermal annealing in air. The resulting nanoneedle arrays exhibit high specific capacitance (1440C cm−2 at 1.0 mA cm−2) and excellent cycling stability while evaluated as promising electrodes for battery-type supercapacitor. An assembled asymmetric supercapacitor (ASC) device using MnCo2O4@Co3O4 as positive electrode and activated carbon (AC) as negative electrode also exhibits a high energy density of 31 Wh kg−1 at a power density of 208.5 W kg−1, furthermore, still remains 14.6 Wh kg−1 even at a higher power density of 3326.6 W kg−1. Importantly, a red light-emitting diode (LED) can be illuminated about 6 min, indicating a great potential for practical applications of the ASC. Besides, the MnCo2O4@Co3O4 exhibits much better electrocatalytic activity for the oxygen evolution reaction (OER). As a result, this work demonstrates a feasible strategy for the design and fabrication of 1D shish-kebab type nanoneedle arrays with multiple functions.